2012
DOI: 10.1088/0031-9155/57/13/4117
|View full text |Cite
|
Sign up to set email alerts
|

Spectral CT imaging of vulnerable plaque with two independent biomarkers

Abstract: The purpose of this paper is to investigate the feasibility of a novel four-material decomposition technique for assessing the vulnerability of plaque with two contrast materials spectral computer tomography (CT) using two independent markers: plaque's inflammation and spotty calcification. A simulation study was conducted using an energy-sensitive photon-counting detector for k-edge imaging of the coronary arteries. In addition to detecting the inflammation status, which is known as a biological marker of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 53 publications
0
35
0
Order By: Relevance
“…This is due to the fact that the lower energy photons carry larger contrast between different tissues than higher energy photons, 9 so a larger fraction was given to the low-kVp source rather than the high-kVp source. The MECT-PC system separated detected photons into five different energy bins with upper thresholds at 33, 49, 65, 80, and 120 keV, which were selected to exploit the K-edge of iodine while the rest of the energy thresholds chosen for a nearly equal number of counts contained in each bin, following the work by Baturin et al 4 The mean energies of the kV spectra were 41.80, 52.51, 56.47, 41.80(98.14), 41.80(52.51), and 52.51 keV for CT-80kVp, CT-120kVp, CT-140kVp, DECT-DS, DECT-SW, and MECT-PC, respectively. For all the CT systems, projection data were simulated with energy-weighted integrals over 1 keV spectral steps.…”
Section: Ct Systems For Comparisonmentioning
confidence: 99%
See 4 more Smart Citations
“…This is due to the fact that the lower energy photons carry larger contrast between different tissues than higher energy photons, 9 so a larger fraction was given to the low-kVp source rather than the high-kVp source. The MECT-PC system separated detected photons into five different energy bins with upper thresholds at 33, 49, 65, 80, and 120 keV, which were selected to exploit the K-edge of iodine while the rest of the energy thresholds chosen for a nearly equal number of counts contained in each bin, following the work by Baturin et al 4 The mean energies of the kV spectra were 41.80, 52.51, 56.47, 41.80(98.14), 41.80(52.51), and 52.51 keV for CT-80kVp, CT-120kVp, CT-140kVp, DECT-DS, DECT-SW, and MECT-PC, respectively. For all the CT systems, projection data were simulated with energy-weighted integrals over 1 keV spectral steps.…”
Section: Ct Systems For Comparisonmentioning
confidence: 99%
“…In this study, the numerical observer framework has been carefully validated on simulated data where the ground truth is known and where the parameters (e.g., plaque feature types, feature size, feature location, equivalent radiation doses of all modalities) can be easily changed to study the impacts of their variation on the classification performance. In the literature, several research studies demonstrated and validated their methods on the assumptions of ideal detectors for investigating the performance of conventional CT and spectral CT. 4,61,62 In order to model more realistic systems, it is suggested that our validation may apply decreased efficiency to the implementations of detectors and energy resolution for further investigation, especially for photon-counting spectral CT, e.g., applying 10% decrease in energy resolution with the quantum detection efficiency varying with photon energy 4 or using 12% full width at half maximum energy resolution. 61 In addition, a material decomposition method is suggested to apply to our data generation to include the possible variation that may obtain from the decomposition method.…”
Section: Dect-sw J=2mentioning
confidence: 99%
See 3 more Smart Citations